Productivity Analysis of Private Sector Banks in India - Ritesh Verma (International Journal of Engineering and Management Research, 2019)
Private sector banks have been responsible for bringing remarkable transformation in the Indian banking but due to presence of highly organized workforce and a complex legal system in India, new challenges emerge in the form of constant endeavour to improve productivity and profitability. An attempt has been made to analyse the performance of private sector banks by studying the productivity parameters discussed as follows.